Controlling the repulsive Casimir force with the optical Kerr effect - Ooi, Chong Heng Raymond; Khoo, Y.Y. (American Physical Society, 2012)
The Casimir force between two plates can be controlled using combinations of dispersive metamaterials and nonlinear materials with the optical Kerr effect. The force can be significantly varied and switched between positive and negative values by changing the intensity of a laser pulse. The switching sensitivity increases for small separation between the plates, providing new possibilities of integrating optical devices into nanoelectromechanical systems.